Development in Sub-Saharan Africa: cultural influences and managers' decision behaviour - Munene, John C.; Smith, Peter B.; Schwartz, Shalom H. (2000)
We explore the relevance of national differences in values to development in sub-Saharan Africa using data from two recent global surveys. The evidence indicates a shared black African culture that emphasizes hierarchy, embeddedness and mastery in contrast to egalitarianism, autonomy and harmony, in keeping with the literature on Africa. Further evidence reveals that African managers stress reliance on formal rules and superiors in reaching decisions, as predicted by their cultural profile. Comparisons with Western European samples indicate that these nations have the opposite cultural profile and that their managers stress self-reliance and consultation with subordinates. Implications of these contrasts for development in Africa and effective collaboration within donor agencies and multinational firms are discussed. - Reproduced
Keywords: Decision behaviour - Sub-Saharan Africa; Managers - Sub-Saharan Africa; Cultural values - Sub-Saharan Africa; Managers